Frederick Nicklaus papers - Nicklaus, Frederick, 1936-1993.
Correspondence, poetry, notes, printed material, and photographs concerning alcoholism, foreign travel, the publishing and editing business, poetry composition, and Nicklaus's relationships with individuals including Tennessee Williams. Correspondents include Rachel Benzaquen, Paul Bowles, Howard Ferguson, Howard Griffin, Francis V. O'Connor, and Harry C. Rutledge.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Poet and editor.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Benzaquen, Rachel -- Correspondence; Bowles, Paul, -- 1910-1999 -- Correspondence; Ferguson, Howard, -- 1908-1999 -- Correspondence; Griffin, Howard, -- 1915-1975 -- Correspondence; O'Connor, Francis V. -- Correspondence; Rutledge, Harry C. -- Correspondence; Williams, Tennessee, -- 1911-1983.; Alcoholism; Editing; Poetry; Publishers and publishing; Travel; Editors; Poets